1992
DOI: 10.1037/0022-3514.63.6.923
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the uncontrollable: Effects of stress on illusory perceptions of controllability.

Abstract: Individuals' failure to exercise actual control over an event might be compensated for by trying to bolster a generalized, subjective sense of control. Control might then be sought by undertaking acts the effect of which on the environment is illusory. This observation led to the hypothesis that stress, which undermines persons' sense of control, would engender illusory perceptions of controllability. The hypothesis was tested in 3 experiments that required Ss to choose between 2 gambling forms. Although the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 41 publications
(58 reference statements)
2
69
0
3
Order By: Relevance
“…Indeed, the Depression Anxiety Stress Scale (DASS-21) required people to indicate their emotional distress in the past two weeks and the analyses on scores of the scale revealed that there were no significant differences between the three groups. The only significant difference between groups was related to stress -high levels of stress were observed in PGTs, in line with studies that have reported stress to be an independent predictor of gambling urges (Elman et al, 2010) and that have demonstrated the role of stress in the onset, maintenance (Coman et al, 1997;Friedland et al, 1992) and relapse of problem gambling (McCartney, 1995).…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, the Depression Anxiety Stress Scale (DASS-21) required people to indicate their emotional distress in the past two weeks and the analyses on scores of the scale revealed that there were no significant differences between the three groups. The only significant difference between groups was related to stress -high levels of stress were observed in PGTs, in line with studies that have reported stress to be an independent predictor of gambling urges (Elman et al, 2010) and that have demonstrated the role of stress in the onset, maintenance (Coman et al, 1997;Friedland et al, 1992) and relapse of problem gambling (McCartney, 1995).…”
Section: Discussionsupporting
confidence: 63%
“…They generally can be thought of as assets to mental health and social functioning. On the one hand, exaggerated self-perceptions, illusions of control, and optimism about the future have been found to be significantly associated with a number of positive factors, such as higher motivation, greater contentment and confidence, more positive self-esteem, and greater use of effective coping strategies (Friedland, Keinan, & Regev, 1992;McKenna, 1993;Scheier & Carver, 1987;Taylor & Brown, 1988). On the other hand, because perceptions of vulnerability are assumed in most theories of preventive behavior to increase the likelihood of preventive or precautionary action (Janz & Becker, 1984;Weinstein, 1993b), optimistic bias would be expected to work against perceptions of vulnerability and thus to slow or impede adoption of precautionary practices and to foster decision-making in directions consistent with optimism and thus inconsistent with fear or risk recognition.…”
Section: Optimistic Bias and Risk Perceptionmentioning
confidence: 99%
“…Indeed, theorists have argued that just-worldbelief maintenance is largely automatic (Lerner & Goldberg, 1999), and evidence suggests that people rely more on immanent justice reasoning to make causal attributions when systematic thought is interrupted (Callan, Sutton, & Dovale, 2010). More generally, people often behave as if they can influence outcomes that they know they cannot, exhibiting signs of illusory control and outright magical belief (Langer, 1975;Pronin, Wegner, McCarthy, & Rodriguez, 2006;Nemeroff & Rozin, 2000), particularly when personal control is lacking (Friedland, Keinan, & Regev, 1992;Keinan, 2002;Malinowski, 1954). Sports fans provide the most pervasive example, often behaving as if their private rituals can influence their team's performance.…”
Section: Introducing "Karmic Investments"mentioning
confidence: 99%